Kendala Yang Dihadapi Mahasiswa Pendidikan Ekonomi Universitas Pamulang Dalam Mengikuti Perkuliahan Daring Pada Mata Kuliah Seminar Proposal Penelitian Selama Masa Pandemi Covid-19 - Syafaatul Hidayati (Universitas Hamzanwadi, 2020)
During the Covid-19 pandemic, the university changed the lecture activities from the original through face-to-face meetings to online lectures. Likewise, researchers also design lectures in such a way that the objectives of the seminar on research proposals can be achieved properly. In the implementation, students face problem in online lectures. The purpose of this study is to determine the obstacles faced by students of economic education at the University of Pamulang (UNPAM) in attending online lectures in the research proposal seminar course during the Covid-19 pandemic. The method used in this research is descriptive qualitative research method. Respondents in this study were 10 students of the S1 Educational Economics Study Program Faculty of Teacher Training and Education (FKIP) Pamulang University (UNPAM) semester VI who took the research proposal seminar course. Based on the results of research on the obstacles faced by Pamulang University economic education students (UNPAM) in attending online lectures in the seminar course for research proposals during the Covid-19 pandemic, it can be concluded that there are internal and external constraints faced by students